Variation Characteristics of Mass-Loss Rate in Dynamic Seepage System of the Broken Rocks. (15th July 2018) - Wang, Luzhen; Kong, Hailing
Abstract : When the collapse column and its adjacent rocks in complex geological structures are disturbed by mining, concomitant fine particle migration, mass loss, and porous structure variation during the water seepage process in broken rocks are the inherent causes for collapse column activation and water inrush. Studying the time-varying characteristics of the mass-loss rate in the dynamic seepage system of the broken rocks is of theoretical importance for the prevention of water inrush from the collapse columns. In this study, the seepage tests of the broken mudstone were carried out using the patented pumping station seepage method, and the time-varying function of the mass-loss rate was generalized. Then, the optimal coefficients in the function of mass-loss rate were computed using the genetic algorithm. At last, the mass-loss rate in the dynamic seepage system of the broken rocks with consideration of the acceleration factor was calculated using Lagrange discrete element method. The results showed that (1) the mass-loss rate was expressed as a time-dependent, exponential function with its coefficient related to the porosity, and its time-varying characteristics were affected by gradation; (2) the time-varying curves with Talbol power exponents less than 0.6 had a rapid change stage and a slow change stage, while the time-varying curves with Talbol power exponents greater than 0.6 had an initial gradual change stage, a rapid change stage and a slow change stage; (3) at the early seepage stage, the mass-loss rate decreased with Talbol power exponent increasing; and (4) after long time seepage, the mass-loss rate was close to zero and unrelated to Talbol power exponent, and the porous structure in broken rocks remained stable with its porosity close to a certain stable value.